2021
DOI: 10.1002/jia2.25786
|View full text |Cite
|
Sign up to set email alerts
|

Global scoping review of HIV prevention research with transgender people: Transcending from trans‐subsumed to trans‐centred research

Abstract: Introduction: Globally, transgender populations are disproportionally impacted by HIV and effective HIV prevention interventions targeting these populations are critically needed. Such interventions require research focused on the specific needs and experiences of transgender people. This methodological review aims to determine the extent to which HIV prevention research has included transgender participants by subsuming them into non-transgender populations, or by centring them either in comparison with other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…The vulnerability of TGW to HIV makes their use of PrEP of vital importance [ 27 , 28 , 29 ]. However, few TGW have been engaged in HIV prevention services [ 5 , 30 ] or PrEP studies [ 31 ], hindering the possibility of meaningful analysis [ 32 ], despite high willingness to use PrEP [ 33 , 34 , 35 ]. In addition, PrEP studies have shown low PrEP continuation among TGW [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…The vulnerability of TGW to HIV makes their use of PrEP of vital importance [ 27 , 28 , 29 ]. However, few TGW have been engaged in HIV prevention services [ 5 , 30 ] or PrEP studies [ 31 ], hindering the possibility of meaningful analysis [ 32 ], despite high willingness to use PrEP [ 33 , 34 , 35 ]. In addition, PrEP studies have shown low PrEP continuation among TGW [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…The first concern is the extent to which trans‐HIV research has emphasized descriptive documentation of risk, pathology and “vulnerabilities” among TGNBCs associated with potential HIV exposure, including sex work, lack of employment opportunities, housing instability, incarceration, violence, substance use and depression [ 7 , 11 , 13 , 17 , 25 , 26 ]. On the one hand, this focus has enabled a greater understanding of several acute challenges faced by TGNBCs, and some findings have been used as essential advocacy tools.…”
Section: Discussionmentioning
confidence: 99%
“…The fifth concern is the under-representation or tokenization of TGNBCs at all levels of the research process [7,15,[20][21][22]. In the current landscape of HIV research, cisgender researchers receive much of the funding for transgender research [15].…”
Section: Methodological and Ethical Concernsmentioning
confidence: 99%
See 2 more Smart Citations